Unibe Chair on Inclusion of People with Disabilities: Contributions to the United Nations Sustainable Development Goals (2030) and to the Social Impact of Higher Education Initiatives in the Dominican Republic - Vargas, Yira; Ortega, Vhyna; Cellucci, Antonella; Mencía-Ripley, Aída (Pedagogika Społeczna Nova, 2025)
Global advocacy for the rights of people with disabilities has led to significant progress in inclusive higher education, supported by initiatives like the UN Convention on the Rights of Persons with Disabilities (2006). Many countries have implemented policies to promote access and participation, aided by technological advancements such as assistive devices (Biel Portero, 2011; Fajardo, 2017). Despite these gains, challenges persist, with disparities in education outcomes between disabled and non-disabled students, as seen in the Dominican Republic (Oficina Nacional de Estadística, 2021). Continued efforts are needed to ensure full inclusion in higher education.